Gender politics and silences on rape in the Nigerian films “tango with me” and “code of silence" (2019)
Current statistics indicate that about two in fifty cases of rape are reported in Nigeria, and the percentage of reported cases has continued to reduce over the years in spite of the observed consistent increase in the number of rape incidents. The burden of rape is more on women who do not have power balance with men to propagate or prosecute a majority of cases. The long silence of women due to the lack of support from male folk shows some kind of gender politics behind rape. Hence, the stigma associated with rape continues to discourage women from reporting rape cases. However, this issue has been continuously explored in many Nigerian (Nollywood) films. But to what extent have Nollywood films contributed to the mobilization of the Nigerian populace toward reducing incidences of rape in Nigeria? Using the framing theory of the media, this article examined two Nigerian films, Tango with Me (dir. Mahmood Ali-Balogun, 2012) and Code of Silence (dir. Emem Isong, 2015), which were purposively selected due to their storylines on rape. The movies were content analysed to highlight the role that men and women play, and the views of society towards rape incidences. The study also examined the gender roles vis-à-vis the stigma and trauma experiences of the victims (mainly the women) and the punishment meted out to the perpetrators of rape. Findings indicated that there is a code of silence; consequently, rape victims (mainly women) are not encouraged to speak out, for fear of losing their mental wellbeing and social status in society. The role of women in rape is passive and submissive to the dictates of a society which valorises patriarchy while the role of men shows aggressive and unrepentant behaviour, which society hardly punishes. The conclusion reached is that Nollywood content producers should help to raise the level of Nigerians’ awareness through their productions to make rape victims see the need to promptly report rape incidents, so that offenders can be punished, and deterrents can begin to emerge.